• Mar 9th 2008, 07:42 PM
confused20
I am having difficulty with the following problem because I do not know how to use the quadratic formula. Can anyone explain step by step on how to do the following problem using the quadratic formula?

x^2/(2.00-x)(1.00-x) = .64

Any input will be greatly appreciated. Thank you.
• Mar 9th 2008, 07:51 PM
topsquark
Quote:

Originally Posted by confused20
I am having difficulty with the following problem because I do not know how to use the quadratic formula. Can anyone explain step by step on how to do the following problem using the quadratic formula?

x^2/(2.00-x)(1.00-x) = .64

Any input will be greatly appreciated. Thank you.

$\frac{x^2}{(2 - x)(1 - x)} = 0.64$

$x^2 = 0.64(2 - x)(1 - x)$

$x^2 = 0.64(2 - 3x + x^2)$

$x^2 = 1.28 - 1.92x + 0.64x^2$

$0.36x^2 + 1.92x - 1.28 = 0$

Now a = 0.36, b = 1.92, and c = -1.28

-Dan
• Mar 9th 2008, 08:43 PM
confused20
How did you arrive at .36x^2?
Thank you a great deal for your response. Can you please tell me how you arrived at .36x^2? I am having difficulty understanding what operation you did to arrive at that figure. Thanks once again for your replay.
• Mar 9th 2008, 08:55 PM
topsquark
Here it is along with the extra step:

$\frac{x^2}{(2 - x)(1 - x)} = 0.64$

$x^2 = 0.64(2 - x)(1 - x)$

$x^2 = 0.64(2 - 3x + x^2)$

$x^2 = 1.28 - 1.92x + 0.64x^2$
=====================================
$x^2 - 0.64x^2 + 1.92x - 1.28 = 0$
=====================================

$0.36x^2 + 1.92x - 1.28 = 0$

Now a = 0.36, b = 1.92, and c = -1.28

-Dan
• Mar 10th 2008, 05:15 AM
confused20
Thank you once again for your replay. To get .36x^2 from .64x^2 do you just subtract by .28? If so, what is the reason that you subtract by .28? Thank you again for all your help.
• Mar 10th 2008, 05:41 AM
topsquark
Quote:

Originally Posted by confused20
Thank you once again for your replay. To get .36x^2 from .64x^2 do you just subtract by .28? If so, what is the reason that you subtract by .28? Thank you again for all your help.

Look at the coefficients oftthe $x^2$ terms. They are 1 and 0.64 respectively. Then 1 - 0.64 = 0.36.

-Dan